2018
DOI: 10.17221/31/2017-swr
|View full text |Cite
|
Sign up to set email alerts
|

Humus substances and soil aggregates in the soils with different texture

Abstract: Tobiašová E., Barančíková G., Gömöryová E., Dębska B., Banach-Szott M. (2018): Humus substances and soil aggregates in the soils with different texture. Soil & Water Res., 13: 44−50.Humus substances (HS) influence the incorporation of carbon into soil aggregates in many ways. In this study the influence of HS and their fractions in the soil on the proportions of carbon (total organic, labile, non-labile) in water-resistant macro-aggregates (WSA) and differences between the amount of carbon in WSA in coarsegrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Soil samples were infused for 24 h. A spectrum analyser (Specord 50 Plus, Analytik Jena, Germany) was used to examine UV/VIs spectra from 300 nm to 700 nm. We calculated the content of humus using Equation (1) [35]:…”
Section: Components Of Humus-isolation Of Fa and Ha Fractionsmentioning
confidence: 99%
“…Soil samples were infused for 24 h. A spectrum analyser (Specord 50 Plus, Analytik Jena, Germany) was used to examine UV/VIs spectra from 300 nm to 700 nm. We calculated the content of humus using Equation (1) [35]:…”
Section: Components Of Humus-isolation Of Fa and Ha Fractionsmentioning
confidence: 99%
“…However, some authors observed a lack of positive responses following HA application to soils [33,34]. A large variety of substrates, with different stages of organic matter transformation, result in extracted HA of varied molecular size, humification degree, the content of polar groups, and aliphatic and aromatic structures [35,36]. Therefore, it is important to test the performance of a single source of HA without extrapolating the results to another source [37].…”
Section: Introductionmentioning
confidence: 99%